Pengalaman Konsumen Dalam Menggunakan Media Sosial Tiktok - Faza Syiham Mu’afa; Triana Rusliana; Helin Garlinia Yudawisastra (Indo Publishing, 2026)
The internet has become increasingly advanced, with the emergence of various social media platforms, including TikTok. By 2025, TikTok had over 1.9 billion global users, with Indonesia being the largest user country (approximately 194.37 million as of July 2025). This has attracted the attention of researchers studying consumer experiences using TikTok. This study aims to analyze and understand consumer experiences using TikTok. This study uses qualitative methods with a content analysis approach and case studies to understand consumer experiences using TikTok. Data were obtained from observations of TikTok video content, user comments, and consumer experiences using TikTok.